Reseña de "Narrators, Narratees, and Narratives in Ancient Greek Literature", De Jong, I., Nünlist, R., Bowie, Angus - Fernández, Claudia Nélida (2006)
Fil: Fernández, Claudia Nélida. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.